Glasfasader för trämoduler. Glass facade for a modular wood construction. - Cederwall, Linnea (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2018)
Abstract Modular construction has significantly developed in the past few decades. The method is preferred due to the quick assembly times and ease of installation. In Sweden, wood is preferred as structural material for the modules. However, modular construction can be aesthetic due to its repetitive façade. Glass facades could be used to ensure an architectonic appeal and break the repetitive pattern. The purpose of the thesis is to investigate how a glass facade can be used in a modular structure using glass and wood. The façade is designed to be industrially manufactured and easily assembled with other facade elements. The thermal conditions and wind loads were asessed assuming that the building will be constructed in Luleå. The outside glass layer thickness has been designed from the load combinations in which the wind pressure was the dominant quasi-static load. The stresses to which the glass layer is exposed has been calculated both analytically and with the finite element method. The facade element consists of three glass layers and a wooden frame. The outside glass plate is laminated and is 14.8 mm thick. The other two are tempered glass plates with a thickness of 4 mm each and two air slots of 18 mm between the glass layers. The tempered glass is treated with a lowemission layer. The U-value of the facade was calculated to be 0.68 W/m2K using the software Spectrum. Laminated wood was used for the wooden frame and goes around the four edges of the glass plates. Each section of the frame is designed as a U-beam with a length of 3 meters. The façade elements are connected to the wooden module with 8x300 mm screws through the U-beam. The web thickness of the U-section was dimensioned to avoid cracking due to drilling. The top and bottom and flange of the U-beam is 100 mm wide and has a thickness of 20 mm. Their purpose is to hold the glass plates in position. Between the glass and the flange, an acrylate adhesive is applied that connects the materials. Sammanfattning Modulbyggnader har utvecklats mycket ...